A Hermeneutical Critique of Indonesian Preachers' Interpretations of Quranic Eschatological Verses: An Analysis of Ad-Dakhīl in YouTube Da'wah on the Last Day - Nurhasan, Muhamad; Anwar, Rosihon; Yunus, Badruzzaman M.; Solehuddin, Solehuddin (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study reviews contemporary Indonesian preachers’ Qur'anic interpretations of end-time events on YouTube, focusing on their quality, validity, and methodology. Using Ibrahim Abdullah Fayed’s Ad-Dakhil criticism approach, it examines how external factors affect interpretive accuracy. Analysis of interpretations by Syaiful Karim, Aam Amiruddin, and Amir Faishol reveals errors from weak Arabic skills, contextual misunderstandings, and subjective readings. The study highlights the need for critical, scientific evaluation standards and interpretive education to ensure responsible and academically sound teachings in the digital era.